PLUM FRUGIVOROUS PHEROMONE TRAP RESULTS OF MONITORING - Khidoyatova Dilorom Mirshakhabovna; Rasulova Madina Shukhratovna; Bobokhonova Muhabbat Abduazimovna; Sharapov Shakhzod Shukhrat ugli (Web of Journals Publishing, 2025)
In this article, information on the results of monitoring the development of plum frugivores using a pheromone trap in the conditions of the Tashkent region is presented.
Keywords: Plum frugivorous, pheromone trap, pest, biological efficiency, monitoring.